1986
DOI: 10.1128/jcm.23.3.627-628.1986
|View full text |Cite
|
Sign up to set email alerts
|

DF-2 septicemia following whirlpool spa immersion

Abstract: We describe the case of a 31-year-old asplenic man who developed DF-2 bacteremia, septic shock, and pneumonia after recreational immersion in a whirlpool spa. The patient did not have a history of dog bite or contact with canine secretions, although he owned two dogs. DF-2 could not be isolated from the whirlpool spa. CDC group DF-2, a slow-growing, fermentative, gramnegative bacillus, can cause fulminant bacteremic infections, particularly in patients who have undergone splenectomy. Septicemia and necrotizing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1987
1987
2010
2010

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…An isolation from a blood culture is similarly rare. Throughout the 1980s, various investigators reported the isolation of Capnocytophaga species from the blood of patients with previously diagnosed neoplasia (6,9,102,110,119,138,146,197,216,224,235,243,316,325).…”
Section: Capnocytophaga Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…An isolation from a blood culture is similarly rare. Throughout the 1980s, various investigators reported the isolation of Capnocytophaga species from the blood of patients with previously diagnosed neoplasia (6,9,102,110,119,138,146,197,216,224,235,243,316,325).…”
Section: Capnocytophaga Sppmentioning
confidence: 99%
“…While cases of C. canimorsus bacteremia in patients with the predisposing factors of alcoholism, splenectomy, and chronic lung disorders (26,49,144,197,263,266,283) and in otherwise healthy individuals (41,49,109,144,283,332) continue to be reported, a number of reports indicate that cancer should be considered a risk factor as well. Table 3 lists the cases of Capnocytophaga bacteremia associated with underlying neoplasia that have been reported (6,9,102,105,110,118,119,137,138,144,146,197,216,224,235,243,269,315,316,325). The association with hematologic malignancies, leukemia and lymphoma, is amply demonstrated.…”
Section: Capnocytophaga Sppmentioning
confidence: 99%
See 1 more Smart Citation